Budgeting system in the management of the construction industry - Нуркашева, Н.; Кукиев A. (Journal of Economic Research & Business Administration, 2017)
This article discusses the main issues and problems in the implementation of budgeting building organizations. To improve the efficiency of material and financial resources, to optimize decision-weighted cost of business – making and evaluation of the possible consequences of these decisions (both positive and negative) of any industry using this technology as budgeting. Thus, budgeting the process of planning the future of the company, the results of which are made out budget system. Implementation of Budgeting helps to create a complete and sufficiently effective management system. The presence of the budgeting procedure is the norm for any company in the developed world, and in recent years has been widely promoted in the Republic of Kazakhstan enterprises. Very important is the fact that the creation of the budgeting system requires the integration and management of information technology, leading to better governance.